(untitled) (Journal of Tropical Pharmacy and Chemistry, 2025)
Estrogen receptor positive (ER+) subtype breast cancer is one of the most common types of cancer in women and requires targeted therapy to improve the effectiveness of treatment. This study aims to explore the potential of active compounds flavonoid group from Etlingera elatior as estrogen receptor alpha (ERα) inhibitors through an in silico approach. Nine compounds were predicted for their pharmacokinetic and toxicity characteristics using SwissADME, then three compounds with the best profiles were selected for molecular docking using AutoDock. The results of the analysis showed that the epicatechin compound had the best binding affinity (–7.57kcal/mol) and a low inhibition constant (Ki 2.80μM), approaching the positive control value of tamoxifen (-10.49kcal/mol; Ki 20.32μM). Epicatechin also showed a good pharmacokinetic profile, was non-toxic, and was conformationally stable in the active pocket of ER+. Thus, epicatechin has the potential as a candidate for natural anticancer agents for the development of ER+ subtype breast cancer therapy based on natural compounds.